Comparison of Two Anterior Reconstructive Techniques in the Treatment of 3-Level and 4 Level Cervical Spondylotic Myelopathy: A Meta-analysis of Last Decade. (24th August 2022) - Wang, Tao; Guo, Junfei; Long, Yubin; Hou, Zhiyong
Study Design: A meta-analysis. Objective: Anterior cervical discectomy and fusion (ACDF) and anterior cervical corpectomy and fusion (ACCF) are widely used in the treatment of cervical spondylotic myelopathy (CSM). However, the clinical outcomes and complications between ACDF and ACCF treating multi-level CSM remain poorly understood. Thus, we performed a meta-analysis to compare the clinical outcomes and complications of the two procedures in the treatment of 3-level and 4-level CSM. Methods: An extensive search of the literature was performed in the English databases of PubMed, Embase, and Cochrane Library and the Chinese databases of CNKI and WANFANG. We collected factors, including demographic data, surgical factors, and complications. Data analysis was conducted with RevMan 5.3 and STATA 12.0. Results: Finally, 14 articles (5429 patients) were included in our study. No significant difference was found in preoperative and 3-month follow-up Japanese Orthopedic Association (JOA) scores, neck disability index, preoperative C2-C7, segmental angle, operation time, as well as the number of dysphagia, hoarseness, cerebral fluid leakage, infection, epidural hematoma, axial pain, hardware breakage, and pseudarthrosis between ACDF and ACCF. However, our findings showed that blood loss ( P < 0.00001), the number of total complications ( P < 0 .00001), C5 palsy ( P = 0.0004), graft dislodgement ( P = 0.02), graft subsidence ( P = 0.0003), and revision surgery ( P = 0.0008) in ACDF were significantly less than in ACCF. Additionally, postoperative and change of C2-C7 ( P < 0.00001), segment angle ( P < 0.00001), and fusion rate ( P = 0.001) in ACDF were significantly higher than in ACCF. Post-operative JOA in ACDF was significantly higher than in ACCF ( P = 0.02). Conclusions: Although the clinical efficacy of both surgeries was similar, ACDF was superior to ACCF in the reconstruction of cervical lordosis and the number of complications in the treatment of 3-level and 4-level CSM.